Asking Tougher Questions in Tough Times - LOW, Irving (Institutional Knowledge at Singapore Management University, 2009)
The recent wave of corporate governance disasters globally raises many eyebrows and burning questions whether audit committees (ACs) are doing the right things to effectively discharge their roles and responsibilities. To further test the integrity and reputation of the Singapore market as a listing gateway for foreign companies in turbulent times like these, the headlines are also reporting a spate of suspected and actual corporate fraud and scandals involving China-based, Singapore listed companies (commonly referred to as “S-chips”). Many angry investors and the public question whether ACs and independent directors are doing their jobs.